Transcriptome analysis of insecticide resistance mechanisms in field populations of the bean flower thrips, Megalurothrips usitatus (Bagnall) - Hongyi Cao; Jiangjiang Yuan; Yanran Wan; Yingxi Tang; Xiaobin Zheng; Jing Wang; Kanghua Qian; Jiuming Feng; Sirui Chen; Youjun Zhang; Qingjun Wu (Ecotoxicology and Environmental Safety)
The bean flower thrips, Megalurothrips usitatus (Bagnall), has caused significant damage to leguminous crops in the Asian tropics and established populations in North America. Ineffective pest control has been reported in multiple regions, raising concerns about food safety risks due to improper insecticide use. To evaluate insecticide susceptibility and the role of detoxification enzyme involvement, resistance monitoring and enzyme activity assays were conducted. RNA sequencing (RNA-seq) and weighted gene co-expression network analysis (WGCNA) techniques validated key gene functions. Results showed that the XW population was resistant to five insecticides, with resistance ratios ranging from 7.17 to 42.90 compared to the reference population. The NJ and YZ populations showed resistance to two and one insecticide, respectively, while the HP population was most susceptible. Elevated cytochrome P450s (CYP450), UDP-glycosyltransferases, and acetylcholinesterases activities were observed in the YZ population. Three CYP450 genes positively correlated with CYP450 activity. Carboxylesterases (CarE) activity was the highest in the XW population, with MusiPT_006325 positively correlated and MusiPT_006095/MusiPT_003750 negatively correlated with CarE activity. Glutathione-S-transferase activity was the highest in the HP population. WGCNA revealed positive correlations between MEblue, MEturquoise, and MEbrown modules and acetamiprid/ novaluron median lethal concentration (LC50) values, but negative correlations with β-cypermethrin, spinetoram, emamectin benzoate, thiamethoxam, and spirotetramat LC50 values. Ten CYP450 genes and three UGT genes were identified as hub genes. Our findings reveal insecticide resistance and the role of detoxification enzymes in M. usitatus, providing valuable insights for developing effective management strategies against this thrips species.